Neurocysticercosis or tuberculoma – Which one has more epileptic potential?. (May 2020) - Pradhan, Sunil; Das, Animesh; Mulmuley, Madhura; Das, Ananya
Abstract: Purpose: The duration of antiepileptic drug (AED) treatment in the management of seizures due to ring enhancing lesions (REL) remains a matter of debate. We undertook a prospective cohort study to look into the seizure patterns and incidence of recurrence in association with two of the most common causes of RELs after gradually stopping AEDs at least 18 months after acheiving seizure control. Methods: Ninety patients with neurocysticercosis (NCC) and twenty-nine patients with tuberculoma were treated with anti-helminthic and anti-tubercular drugs according to current recommended guidelines, and followed up for a minimum of 2 years after the last seizure free day. In every patient included in the study, AEDs were tapered within six months of attaining a seizure-free interval of 18 months. We looked at the incidence of recurrent seizures after stopping AEDs in both groups of patients. Results: The frequency of baseline seizures (2.1 vs 1.5 per year, p < 0.001) and number of antiepileptic drugs (2.12 vs 1.48, p < 0.001) were greater in patients with NCC than those with tuberculoma. Patients with NCC had a greater incidence of recurrent seizures (1.17 vs 0.07 in the next six months, p < 0.001) after stopping the AEDs. The median interval to seizure recurrence after stopping AEDs was 2.2 months in patients with NCC. Conclusions: Among RELs, NCC lesions have a greater epileptogenic potential than tuberculomas. AEDs can be tapered in patients with tuberculoma after a seizure free period of 18 months with a very low risk of recurrence.